Characteristics and trends of regional labour markets in transition economies: Empirical evidence from Romania - Ella Kállai; Iulia Traistaru (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 1998)
Regional labour markets disparities have remained stable in Romania, as it is the case in Poland. In spite a huge output decline in the first years of transition, the process of adjustment to sectoral shifts has been slow. We find a negative relationship between regional unemployment rates and regional sectoral reallocation, but no correlation between these two variables. The most intense labour reallocation - both job creations and job destructions have taken place in regions with an industrial profile. Job destruction is predominant in agricultural regions. The estimated local unemployment elasticity of wages is negative suggesting the presence of a wage curve in Romania. Inter-regional migration flows are not correlated with regional unemployment rates while the availability of housing plays an important role in the decision to move across regions. While the agricultural regions are net senders, the industrial and diversified regions are net receivers. The absorption capabilities have declined in both industrial and diversified regions, faster in the industrial regions. It seems that the outflows of migrants from agricultural regions respond to the absorption capability of industrial rather than diversified regions.
Keywords: L16; J21; J64; R23; 330; transition economies; regional specialisation; regional unemployment; regional job reallocation; wage flexibility; regional labour